Inflammation and Oxidative Stress: Potential Targets for Improving Prognosis After Subarachnoid Hemorrhage - Wu, Fan; Liu, Zongchi; Li, Ganglei; Zhou, Lihui; Huang, Kaiyuan; Wu, Zhanxiong; Zhan, Renya; Shen, Jian (Frontiers in Cellular Neuroscience, 2021)
Subarachnoid hemorrhage (SAH) has a high mortality rate and causes long-term disability in many patients, often associated with cognitive impairment. However, the pathogenesis of delayed brain dysfunction after SAH is not fully understood. A growing body of evidence suggests that neuroinflammation and oxidative stress play a negative role in neurofunctional deficits. Red blood cells and hemoglobin, immune cells, proinflammatory cytokines, and peroxidases are directly or indirectly involved in the regulation of neuroinflammation and oxidative stress in the central nervous system after SAH. This review explores the role of various cellular and acellular components in secondary inflammation and oxidative stress after SAH, and aims to provide new ideas for clinical treatment to improve the prognosis of SAH.